PENDEKATAN HAK ASASI MANUSIA DEBITOR DAN KREDITOR DALAM PENGUJIAN UNDANG-UNDANG KEPALITIAN DAN PENUNDAAN KEWAJIBAN MEMBAYAR UTANG DIMASA MENDATANG (Solusi, 2023)
The Human Rights Approach of Debtors and Creditors in Testing Bankruptcy Laws and Postponing Bankruptcy Obligations to Pay Debts in the Future is discussed in this study, Along with how Indonesia's legal system's state or evolution with regard to bankruptcy law and the suspension of debt payment responsibilities. Indonesia. In this study, a normative research methodology is used to investigate problems with the law and pertinent literature. According to the study's findings, the Bankruptcy Law and Postponement of Obligation to Pay Future Debt regulates the human rights approach between debtors and creditors when it comes to testing the law. Law Number 37 of 2004 Concerning Bankruptcy and Postponement of Debt Payment Obligations is the name of this regulation. By filing for bankruptcy or requesting a suspension of their debt payment responsibilities, debtors can reach an agreement with their creditors regarding the repayment of their debts. A delay in payment of debt is a time period allotted by law in line with a Commercial Judge's Decision, during which the creditor and debtor can discuss how to pay their debts by drafting a payment plan for all or any of those debts, including by restructuring the debt. Either the debtor or the creditor may ask for a suspension of the debt payment obligations.